Berenstain Bears' (The): trouble at school - Berenstain, Stan (New York: Random House, 1986)
When Brother Bear returns to school after being out sick, he gets into a mess that gets worse until Gramps given him some advice.
Keywords: Bears--Fiction.; Schools--Fiction.